Modified contrast microinjection technique to facilitate chronic total occlusion recanalization. Issue 6 (10th September 2015) - Carlino, Mauro; Ruparelia, Neil; Thomas, Gavin; Brooks, Matthew; Uretsky, Barry F.; Brilakis, Emmanouil S.; Karmpaliotis, Dimitri; Hanratty, Colm; Walsh, Simon; Spratt, James; Colombo, Antonio
Abstract : Objectives: To assess the efficacy and safety of the modified contrast microinjection technique to facilitate chronic total occlusion recanalization. Background: The success rate of chronic total occlusion percutaneous coronary intervention (CTO‐PCI) does not exceed 90% even in the most experienced centres. We have previously demonstrated that a large volume of contrast injected into the subintimal space can facilitate recanalization but is limited by a risk of serious complication. The aim of this study was to assess the application, efficacy and safety of a modified contrast microinjection technique that utilizes the injection of a much smaller volume of contrast in CTO‐PCI. Methods: A retrospective analysis of patients in whom the modified microinjection technique was utilised in patients undergoing CTO‐PCI at five tertiary centres was conducted. Results: Of 1, 192 patients who underwent CTO‐PCI, the microinjection technique was used in 59 patients (4.7%). The majority of CTOs treated were in the right coronary artery (79.7%), were of high complexity and 35.6% of lesions had a least one previously failed PCI attempt. The modified microinjection technique was used for more than one indication in 7 (11.9%) of patients. The success rate was 81.4%. There were no procedural complications related to the use of the reported modified microinjection. Conclusion: Initial experience with the modified microinjection demonstrates that it can be performed safely, is reproducible, and is broadly applicable. Whilst not required for all CTO procedures it can be a helpful adjunctive tool to increase the likelihood of success especially in complex, or refractory cases, without compromising the safety of the procedure. © 2015 Wiley Periodicals, Inc.